Perancangan buku We Love And We Care Pengenalan Hewan dilindungi kepada anak- anak - Dwi Puji Prabowo; Auria F. Yogananti; Erisa Adyati; Shofy Ali Zaky; Ayyub H. B. Nurmana (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
The extermination of animal populations is increasing, due to increased poaching and wildlife trade. This requires learning about caring for animals. Books play a very important role in the world of education, so that the learning process cannot be separated from the learning environment in the form of books. This design aims to produce a book concept about protected animals in Indonesia as an informative medium, providing scientific insight and knowledge about protected animals in Indonesia. The research method used is qualitative as a method for searching for data in the form of verbal data and in visual form. Needs analysis data will be used to obtain a concept for designing the book "We Love And We Care" about protected animals in Indonesia. The book "We Love And We Care" is expected to attract children's interest in reading and loving the environment, especially protected animals.